1994
DOI: 10.2307/5585
|View full text |Cite
|
Sign up to set email alerts
|

Population Cycles of Forest Lepidoptera: A Maternal Effect Hypothesis

Abstract: Summary1. Many species of forest Lepidoptera have cyclic population dynamics. Although there are numerous potential causes, including interactions with predators, parasitoids, pathogens, and food-plant quality, strongly density-dependent interactions are often difficult to demonstrate. Both autocorrelation analysis and attractorreconstruction methods have recently been applied to a number of species' time series. Results suggest that complex dynamics, i.e. cycles or deterministic chaos, may be more prevalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
202
2
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(214 citation statements)
references
References 82 publications
8
202
2
2
Order By: Relevance
“…In the presence of environmental fluctuations, the lag created by the delayed life-history effect typically also increases population variability and decreases its predictability (Benton et al 2001b;Beckerman et al 2002). In addition, maternal effects can theoretically lead to long-term deterministic population dynamical patterns such as population cycling seen in forest Lepidoptera and many microtine rodents (Ginzburg & Taneyhill 1994;Ginzburg 1998;Inchausti & Ginzburg 1998). Understanding the causes of fluctuations in population size and the interplay between the environment and density dependence is a key goal of current population ecology (Saether 1997;Bjørnstad & Grenfell 2001;Coulson et al 2001;CluttonBrock & Coulson 2002;Greenman & Benton 2003) and is crucial for predictive population modelling for management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of environmental fluctuations, the lag created by the delayed life-history effect typically also increases population variability and decreases its predictability (Benton et al 2001b;Beckerman et al 2002). In addition, maternal effects can theoretically lead to long-term deterministic population dynamical patterns such as population cycling seen in forest Lepidoptera and many microtine rodents (Ginzburg & Taneyhill 1994;Ginzburg 1998;Inchausti & Ginzburg 1998). Understanding the causes of fluctuations in population size and the interplay between the environment and density dependence is a key goal of current population ecology (Saether 1997;Bjørnstad & Grenfell 2001;Coulson et al 2001;CluttonBrock & Coulson 2002;Greenman & Benton 2003) and is crucial for predictive population modelling for management.…”
Section: Introductionmentioning
confidence: 99%
“…Inference has typically been made from information contained in time-series, such as the period and shape (e.g. time reversibility) of population cycles (Ginzburg & Taneyhill 1994;Ginzburg 1998;Inchausti & Ginzburg 1998;Turchin & Hanski 2001;Shaw et al 2004), or the relationship between population perturbations or size and the life history of cohorts of individuals (Albon et al 1987;Myers et al 1998;Erelli & Elkinton 2000;Forchhammer et al 2001;Beckerman et al 2002Beckerman et al , 2003Reid et al 2003). A number of experiments have been conducted to investigate the strength of maternal influence on individual performance in a range of animals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When this is the case, the reproduction and survival of individuals reflect not only current environmental conditions, but also the environmental conditions experienced by their progenitors (reviews in Mousseau & Fox 1998;Lindströ m 1999;Metcalfe & Monaghan 2001), which can significantly affect population dynamics (Lindströ m 1999;Beckerman et al 2002;Benton et al 2005). Population models incorporating intergenerational effects typically assume there is a positive relationship between the parental environment and offspring quality (Ginsburg & Taneyhill 1994). However, several studies have shown that, in order to produce more offspring or lessen the burden on themselves, parents may produce poorer quality offspring when conditions are favourable because it is precisely when conditions are favourable that offspring quality is least likely to affect recruitment (Bernardo 1996;Sinervo et al 2000;Plaistow et al 2006;Russell et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…U (x, t) → U (x − ct) ∪ U (x + ct). Consider, for instance, the front propagating to the right, U (x, t) = U (ξ) where ξ = x − ct, which is the solution of the following equation (in dimensionless variables): 14) corresponding to the conditions at in nity as U (ξ) → 0 for ξ → ∞ and U (ξ) → 1 for ξ → −∞.…”
Section: Loss Of Monotonicitymentioning
confidence: 99%
“…Delayed density dependence is thought to be one of the main factors causing population uctuations (Berryman and Turchin 1997). The most commonly considered causal mechanisms are resource competition (Hansen et al 1998), cannibalism (Briggs et al 2000), and maternal e ects (Ginzburg and Taneyhill 1994) where the nutritional environment of the parental generation can in uence the growth and reproductive potential of the next generation. Delays may also occur as a consequence of developmental time and/or interaction between individuals of di erent stages (Royama 1981, Hastings 1984.…”
Section: Introductionmentioning
confidence: 99%